Isolation and characterization of a cytotoxic metabolite of Talaromyces bacillosporus. - Ishii, K (1995)
A cytotoxic metabolite, talarotoxin, was isolated from a fungus, Talaromyces bacillosporus IFO 8397, cultured on rice. The structure of the toxin was elucidated and found to contain a pyrrolizidinedione connected with a trans delta 1-octalin through a conjugated triene.